Determination of stevioside and rebaudioside a in Stevia rebaudiana leaves via preparative HPLC - Aliaa Diyana, Abdul Hisham (2012)
Stevia rebaudiana leaves, also known as sweet leaf. It has been used as sweetener for centuries in South America. Stevia rebaudiana leaves contain noncaloric sweeteners (steviol glycosides) whose consumption could exert beneficial effects on human health. Steviol glycosides are considered safe. The aim of present study was to determine qualitative of stevioside and rebaudioside A which compounds of steviol glycosides consist in Stevia leaves by soxhiet extraction method using Waters preparative HPLC autopurification system. Samples were sequentially extracted by soxhiet extraction method using methanol solvent and the analytes separated by Waters XBridge C 18 column (150 mm x 4.6 mm I.D., 5tm). This HPLC analytical column, performed with a mobile phase in isocratic mode elution consisting of acetonitrile/water (80:20 v/v). Stevioside were the most abundant steviol glycosides found followed rebaudioside A in samples of Stevia (n = 5) from Malaysia. This proposed Waters preparative HPLC autopurification system can be applied for further analysis in this study for the routine quality control of Stevia leaves and their commercial preparations.